ANALISIS PEMBERIAN REWARD DAN PUNISHMENT TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR NEGERI 12 KOTO BARU - Muhammad Sukron; Yulia Darniyanti; Yoyok Dwi Purnama (STKIP Subang, 2024)
Based on the author's observations at SDN 12 Koto Baru during the teaching and learning activities for Natural and Social Sciences (IPAS), it was noted that the fifth- grade class consists of 18 students. On Wednesday, July 12, 2023, during the PLP implementation, the author observed that several students were quite passive during the lessons. About five students were only listening to the teacher's explanations and taking notes without actively participating. When questioned, they often pretended to understand the material even though they did not fully grasp it. Two of these students were found outside the classroom when the lesson began, one student requested to leave the class for an unrelated reason, and around five students sitting in the back row frequently created disturbances, disrupted their classmates, worked on homework for other subjects, did not pay attention to the teacher's explanations, ate in class, and one even slept during the lesson. The author concluded that implementing rewards and punishments could be an effective method to motivate students, boost their enthusiasm, and encourage responsibility in completing their tasks. By providing rewards or applying penalties, students are likely to be more focused and improve their learning outcomes. If students exhibit talent in non-academic activities, participating in competitions or extracurricular activities can be an opportunity to hone their skills and enhance their motivation. Receiving certificates or awards from these activities can also inspire students to be more enthusiastic and engaged. If we observe that students have talents, participating in competitions and encouraging them to take part can help in nurturing these talents, even though not all students may be interested, as they tend to be more active in non- academic areas.